SSR and 18S rDNA based molecular profiling of Neopyropia yezoensis (Rhodophyta) in China: insight into genetic impact of laver aquaculture on wild resource - Xu, Hui; Jia, Rujie; Liang, Zhourui; Lu, Xiaoping; Wang, Wenjun (Frontiers in Marine Science, 2023)
Neopyropia yezoensis is a typical intertidal seaweed and an indispensable species for conservation of seaweed resource. As one of the most important marine vegetables, the culture area of N. yezoensis has been largely increasing in the past decade and ranks the second highest among all the farmed seaweeds in China. Whether large-scale cultivation of N. yezoensis laying a genetic impact on wild resource remains unknown. In this study, SSR markers and 18S rDNA were applied for diversity and genetic structure analysis of 22 N. yezoensis populations from North China. Twenty-two haplotypes were generated from 352 18S rDNA sequences and only 3 haplotypes were shared by both cultivated and wild populations. Eleven polymorphic SSR markers were developed and distinguished the cultivated populations from the wild ones. The average polymorphism of the cultured N. yezoensis populations was higher than the wild ones, with the percentage of polymorphic loci being 90.91% in most cultivated populations. It indicated the cultivated N. yezoensis are diversified and divergent from the wild resource in China. The genetic differentiation between the cultivated populations and the wild ones decreased with increasing cultivation time, suggesting a possible long-term and slow process for the genetic impact of N. yezoensis aquaculture on wild resource. The wild populations were grouped into two distinct clades by SSRs, with one distributed around the intersection between the Yellow Sea and the Bohai Sea, where the populations were characterized by a specific 18S rDNA haplotype. These findings provided useful insights into germplasm conservation, genetic breeding and improvement of farming of N. yezoensis.